Gasification of municipal solid waste blends with biomass for energy production and resources recovery: Current status, hybrid technologies and innovative prospects. (February 2021) - Hameed, Zeeshan; Aslam, Muhammad; Khan, Zakir; Maqsood, Khuram; Atabani, A.E.; Ghauri, Moinuddin; Khurram, Muhammad Shahzad; Rehan, Mohammad; Nizami, Abdul-Sattar
Abstract: This paper critically reviews the current status of utilization of municipal solid waste and biomass blends for energy and resources recovery together with identifying the opportunities for future development in technological equipment and physicochemical waste compositions involved in such complex processes. Among numerous thermochemical conversion techniques, gasification of municipal solid waste with different biomass blends has unveiled as an auspicious technology to develop a sustainable waste management system that would substantially reduce pollution and maximize energy and materials recovery. Municipal solid wastes and biomass have different properties and elemental compositions and are abundantly available. These materials have the potential to produce various types of value-added products in terms of energy and chemicals through the gasification process. Recently, hybrid systems have been introduced with simple gasification technologies in terms of fuel oxidation system, plasma torch, or some biochemical conversion systems to enhance the process efficiency, energy, economics, quality, the yield of syngas, and to alter the composition of gaseous products. Consequently, gasification of biomass and waste would be the most suitable option to reduce toxic elements and harmful gases for the surroundings. For instant, ecological influence is not the real issue for limitation of biomass and waste gasification development, while a feasible economic return could appeal to investors and initiate its commercialization. Energy and resource recovery is assessed as an integrated approach to overcoming limitations. Also, techno-economic and environmental impact, life cycle assessment, and their implications are discussed in detail. Key bottlenecks that need urgent attention to facilitate global recognition of hybrid technology are highlighted. Graphical abstract: Image 1 Highlights: Blending practices of municipal solid waste with biomass are critically reviewed. Hybrid configurations of gasification are assessed to overcome technological limitations. Gasification of biomass and waste could reduce toxic elements and harmful gases. Practical approaches of the gasification process are till on an initial point of utilization. Hybrid systems with gasification would enhance process efficiency and energy.